Analisis Aktivitas Quercetin Moringa oleifera terhadap Inhibisi Acetylcholinesterase (AChE) pada Terapi Alzheimer dengan Pendekatan In Silico - JULIA ANGELINA SAFITRI; TAMAM JAUHAR; PETER GUNAWAN TANDEAN; ERIC MAYO DAGRADI (Universitas Hang Tuah, 2025)
Many plants contain active compounds that can be used to treat various diseases. One of these plants is Moringa oleifera Lam. (drumstick tree), which is known for its benefits in treating Alzheimer’s disease. The active compound quercetin found in Moringa oleifera has the ability to inhibit acetylcholinesterase (AChE), one of the primary causes of Alzheimer’s disease. Quercetin also has similar potential and functions to donepezil, a drug commonly used in Alzheimer’s therapy. This study aimed to examine the role of quercetin in inhibiting AChE as part of Alzheimer’s therapy using an in silico approach. The research utilized molecular docking, pharmacokinetic ADME predictions, and toxicity predictions to evaluate the active compound quercetin. The results showed that quercetin has similar potential to donepezil in inhibiting AChE, as they both share the same binding sites. Pharmacokinetic predictions revealed that quercetin is well-absorbed in the intestine and has better skin permeability compared to donepezil, although its ability to cross the Blood-Brain Barrier (BBB) is limited. Quercetin has a limited distribution in the body, a high binding affinity to plasma proteins, and acts as an inhibitor of CYP1A2 and CYP2C9 enzymes. Additionally, quercetin is effectively excreted by the body. It is predicted to have potential as an oral medication and is categorized as a class III compound based on its LD50 toxicity value Keywords : Alzheimer’s disease, In silico, Acetylcholinesterase (AChE), Moringa oleifera, Quercetin